Transformation of UK Counter-Terrorism Policy Post-9/11: : Balancing Security, Liberty, and Emerging Threats - Kamruzzaman, Muhammad (The Jahangirnagar Review, 2025)
The United Kingdom’s counter-terrorism policy has undergone significant transformation since the events of 11 September 2001. The scale and nature of the terrorist threat posed by extremist groups, particularly from Islamic radicalism, prompted an overhaul of both legal frameworks and security measures. This paper assesses the extent to which these changes have reshaped the UK’s approach to counter-terrorism. Key developments include the introduction of anti-terrorism legislation such as the Terrorism Act 2000 and subsequent updates, including the Prevention of Terrorism Act 2005 and the Counter-Terrorism and Security Act 2015. These laws expanded government powers to detain, monitor, and restrict individuals suspected of involvement in terrorism. Additionally, the establishment of specialized security agencies and increased collaboration with international partners has strengthened intelligence gathering and response. However, these measures have also raised concerns over civil liberties, the balance between security and privacy, and the effectiveness of preventive strategies. This paper explores the evolving nature of UK counter-terrorism policies, examining their impact on national security, individual freedoms, and the broader societal context in which they are implemented, arguing that while significant progress has been made, ongoing challenges remain in adapting to emerging threats.